Lactobacillus acidophilus attenuates Salmonella-induced intestinal inflammation via TGF-β signaling. Issue 1 (December 2015) - Huang, I-Fei; Lin, I-Chun; Liu, Pei-Feng; Cheng, Ming-Fang; Liu, Yen-Chen; Hsieh, Yao-Dung; Chen, Jih-Jung; Chen, Chun-Lin; Chang, Hsueh-Wei; Shu, Chih-Wen
Abstract Background Salmonella is a common intestinal pathogen that causes acute and chronic inflammatory response. Probiotics reduce inflammatory cytokine production and serve as beneficial commensal microorganisms in the human gastrointestinal tract. TGF-β (transforming growth factor β)/SMAD and NF-κB signaling play important roles in inflammation in intestinal cells. However, the involvement of the signaling in regulating inflammation betweenSalmonella and probiotics is not fully understood. Methods L.acidophilus and prebiotic inulin were used to treat human intestinal Caco-2 cells prior to infection withSalmonella . The cells were harvested to examine the cytokines and MIR21 expression with immunoblotting and real-time PCR. NF-κB and SMAD3/4 reporter vectors were transfected into cells to monitor inflammation and TGF-β1 signaling, respectively. Results In this study, we showed that the probioticL. acidophilus decreasedSalmonella- induced NF-κB activation in human intestinal Caco-2 cells. Expression of the inflammatory cytokines, TNF-α and IL-8, inL. acidophilus -pretreated cells was also significantly lower than that in cells infected withSalmonella alone. Moreover, TGF-β1 and MIR21 expression was elevated in cells pretreated withL. acidophilus or synbiotic, a combination of inulin andL. acidophilus, compared to that in untreated cells or cells infected withS. typhimurium alone. By contrast, expression of SMAD7, a target of MIR21, was accordingly reduced in cells treated withL. acidophilus or synbiotics. Consistent with TGF-β1/MIR21 and SMAD7 expression, SMAD3/4 transcriptional activity was significantly higher in the cells treated withL. acidophilus or synbiotics. Furthermore, TGF-β1 antibody antagonized the SMAD3/4 and NF-κB transcriptional activity modulated byL. acidophilus in intestinal cells. Conclusion Our results suggest that the TGF-β1/MIR21 signaling pathway may be involved in the suppressive effects ofL. acidophilus on inflammation caused byS. typhimurium in intestinal Caco-2 cells.